The evolution of social media marketing: A comprehensive systematic review of current trends, challenges, and future insights - Prasetya, Muhammad Dimas; Ananda, Puteri; Ananda, Beby Karina Fawzeea Sembiring; Fadli, Fadli (Jurnal Pendidikan Teknologi Kejuruan, 2025)
This study systematically reviews the evolving landscape of social media marketing (SMM), focusing on key trends, challenges, and opportunities, drawing insights from 23 empirical studies published between 2020 and 2025. The research follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, utilizing bibliometric analysis and data visualization tools like RStudio, VOSviewer, Python, and Microsoft Excel to analyze the data. The review identifies the dominant role of influencer marketing, user engagement, and the integration of emerging technologies, such as artificial intelligence (AI) and big data analytics, in shaping modern marketing strategies. It highlights the significance of platform-specific strategy, particularly on Instagram, Facebook, TikTok, Twitter, and YouTube, where influencer credibility and parasocial relationships have become crucial drivers of consumer behavior and brand loyalty. The study also uncovers the impact of live shopping, augmented reality (AR), and immersive content on enhancing consumer engagement and influencing purchase intentions. Despite the progress, significant challenges remain, including measurement issues, the rapid evolution of platforms, and the complexity of defining engagement across platforms. The review suggests integrating AI-based tools and cross-platform studies to gain deeper insights into consumer behavior. Additionally, it emphasizes the importance of authenticity, transparency, and personalized content to build long-term relationships with consumers. The findings offer practical strategies for marketers and researchers, urging a shift towards more personalized, data-driven, and emotionally resonant content strategies to navigate the dynamic digital marketing landscape.